From Olocausto to Shoah: Naming Genocide in 21st-Century Italy - Robert S. C. Gordon (Modern Languages Open, 2015)
The article examines patterns in the terminology used to label the Nazi genocide of the Jews, focussing in particular on the case study of late 20th-century and early 21st-century Italy. It argues that a very specific and unusual shift occurred in this context, in that the long-established and most common term for the genocide across many languages, “The Holocaust”, was displaced in this period within Italian media, official and public-sphere language by the more arcane, but in certain respects more “approved” term, “Shoah”.  The article looks at evidence to establish that this shift occurred and examines possible the reasons for and implications behind the shift and what it tells us about developments in Holocaust memorialization and cultural knowledge at the turn of the millennium. This article is published under a CC-BY license https://creativecommons.org/licenses/by/3.0/